2001
DOI: 10.4315/0362-028x-64.9.1430
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Commonly Used Disinfectants for the Inactivation of Calicivirus on Strawberry, Lettuce, and a Food-Contact Surface

Abstract: Norwalk and Norwalk-like viruses (NLVs) are important causes of foodborne gastroenteritis in restaurant-related outbreaks. Efficacy of common disinfection methods against these viruses on food-contact surfaces and fresh produce is not known partially because of their nonculturability. Seven commercial disinfectants for food-contact surfaces and three sanitizers for fruits and vegetables were tested against cultivable feline calicivirus (FCV). Disks of stainless steel, strawberry, and lettuce were contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 21 publications
3
83
2
Order By: Relevance
“…The effect on the genomic copy number was significant but lower than that of other biocidal products such as sodium hypochlorite for example; again, this finding is in accordance with the results of Fraisse et al (2011). FCV seems to be more sensitive to sodium hypochlorite and to PAA than MNV (Gulati et al 2001;Baert et al 2009b;D'Souza and Su 2010;Fraisse et al 2011;Park and Sobsey 2011;Kim et al 2012;Vimont et al 2015); therefore FCV could overestimate the effect of these two biocides on HuNoV.…”
Section: Discussionsupporting
confidence: 83%
“…The effect on the genomic copy number was significant but lower than that of other biocidal products such as sodium hypochlorite for example; again, this finding is in accordance with the results of Fraisse et al (2011). FCV seems to be more sensitive to sodium hypochlorite and to PAA than MNV (Gulati et al 2001;Baert et al 2009b;D'Souza and Su 2010;Fraisse et al 2011;Park and Sobsey 2011;Kim et al 2012;Vimont et al 2015); therefore FCV could overestimate the effect of these two biocides on HuNoV.…”
Section: Discussionsupporting
confidence: 83%
“…The application of higher concentrations is limited due to sensorial aspects. Prolonging the chlorine treatment would not be useful to increase the efficacy of chlorination since two studies showed that a contact time beyond 10 min made little difference in antiviral activity towards FCV Gulati et al, 2001). EFSA Journal 2011;9(7):2190…”
Section: Efficacy Of Decontamination Methods On Fresh Producementioning
confidence: 99%
“…The application of 200 ppm chlorine to treat strawberries and lettuce did not result in an additional reduction of FCV compared to washing with tap water (Gulati et al, 2001). …”
Section: Efficacy Of Decontamination Methods On Fresh Producementioning
confidence: 99%
See 1 more Smart Citation
“…Chlorinated water (100-300 ppm chlorine) has also been shown to reduce E. coli O157:H7 inoculated strawberries by less than 1.5 log 10 CFU/g 36,55 . Moreover, chlorinated water (800 ppm chlorine) was reported to reduce Feline calicivirus (FCV) by only 1 log 10 FCV/g on the strawberry 16 . These results can be attributed to the surface structure of the strawberry fruit.…”
Section: Introductionmentioning
confidence: 99%